Morphological Spelling: Present-tense Verb Inflection in the Early Editions of The Book of Good Maners - Rutkowska, Hanna (International Journal of English Studies, 2020)
This study aims at contributing to the discussion on the role of the early printers in the regularisation and standardisation of the English spelling. It assesses the degree of early printers’ (in)consistency concerning morphological spelling, in particular the spelling of third person singular present tense (indicative) inflectional endings of verbs in six editions of The book of good maners (1487–1526), printed by William Caxton, Richard Pynson and Wynkyn de Worde. The analysis suggests that early printers could have been interested in regularising spelling already before normative guidance from scholars became available in the form of grammars and spelling books, that is before the middle of the sixteenth century. However, the levels of the printers’ spelling consistency varied, depending on the particular printing house and edition.